Propuesta de mejora al proceso orientación y desarrollo estudiantil de la ESPAM “MFL” - Alcívar Chica, María José (2021)
This research work was carried out with the purpose of elaborating a proposal for the improvement of the Student Orientation and Development process at Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", to achieve quality in its processes. The methodology used was field research, which allowed the extraction of data and information through the use of interviews and observation to identify the current state of the intervened processes. Subsequently, the added value analysis (AVA) was applied, to detect the main flaws in the different procedures and activities studied, which did not generate value for the client and the institution. The results obtained showed indices of (AVA) and (AVA -ESIA) below the average efficiency, so improvements were incorporated to the processes under study in order to achieve better results. At the end of the investigation, it could be concluded that it is necessary for the institution to establish a continuous management system for all its processes so that inefficiencies in them can be identified in time. According to the AVA - ESIA in the three studied sub-processes of the Orientation and Development process, some of its activities should be automated; criteria that was taken into account for the redesign of the processes, which was socialized with the Polytechnic Extension and Welfare staff, also showing an increase of the efficiency level putting the proposal into practice.